Resolution of inflammation in obesity-induced liver disease - Rius, Bibiana; López-Vicario, Cristina; González-Périz, Ana; Morán-Salvador, Eva; García-Alonso, Verónica; Clària, Joan; Titos, Esther (Frontiers in Immunology, 2012)
Low-grade inflammation in adipose tissue is recognized as a critical event in the development of obesity-related co-morbidities. This chronic inflammation is powerfully augmented through the infiltration of macrophages, which together with adipocytes, perpetuate a vicious cycle of inflammatory cell recruitment and secretion of free fatty acids and deleterious adipokines that predispose to greater incidence of metabolic complications. In the last decade, many factors have been identified to contribute to mounting unresolved inflammation in obese adipose tissue. Among them, pro-inflammatory lipid mediators (i.e. leukotrienes) derived from the omega-6 polyunsaturated arachidonic acid have been shown to play a prominent role. Of note, the same lipid mediators that initially trigger the inflammatory response also signal its termination by stimulating the formation of anti-inflammatory signals. Resolvins and protectins derived from the omega-3 polyunsaturated docosahexaenoic and eicosapentaenoic acids have emerged as a representative family of this novel class of autacoids with dual anti-inflammatory and pro-resolving properties that act as “stop signals” of the inflammatory response. This review discusses the participation of these endogenous autacoids in the resolution of adipose tissue inflammation, with a special emphasis in the amelioration of obesity-related metabolic dysfunctions, namely insulin resistance and non-alcoholic fatty liver disease.